Enzymatically Cross-Linked Silk Fibroin-Based Hierarchical Scaffolds for Osteochondral Regeneration - Ribeiro, V. P. (2019)
Osteochondral (OC) regeneration faces several limitations in orthopedic surgery, owing to the complexity of the OC tissue that simultaneously entails the restoration of articular cartilage and subchondral bone diseases. In this study, novel biofunctional hierarchical scaffolds composed of a horseradish peroxidase (HRP)-cross-linked silk fibroin (SF) cartilage-like layer (HRP-SF layer) fully integrated into a HRP-SF/ZnSr-doped β-tricalcium phosphate (β-TCP) subchondral bone-like layer (HRP-SF/dTCP layer) were proposed as a promising strategy for OC tissue regeneration. For comparative purposes, a similar bilayered structure produced with no ion incorporation (HRP-SF/TCP layer) was used. A homogeneous porosity distribution was achieved throughout the scaffolds, as shown by micro-computed tomography analysis. The ion-doped bilayered scaffolds presented a wet compressive modulus (226.56 ± 60.34 kPa) and dynamic mechanical properties (ranging from 403.56 ± 111.62 to 593.56 ± 206.90 kPa) superior to that of the control bilayered scaffolds (189.18 ± 90.80 kPa and ranging from 262.72 ± 59.92 to 347.68 ± 93.37 kPa, respectively). Apatite crystal formation, after immersion in simulated body fluid (SBF), was observed in the subchondral bone-like layers for the scaffolds incorporating TCP powders. Human osteoblasts (hOBs) and human articular chondrocytes (hACs) were co-cultured onto the bilayered structures and monocultured in the respective cartilage and subchondral bone half of the partitioned scaffolds. Both cell types showed good adhesion and proliferation in the scaffold compartments, as well as adequate integration of the interface regions. Osteoblasts produced a mineralized extracellular matrix (ECM) in the subchondral bone-like layers, and chondrocytes showed GAG deposition. The gene expression profile was different in the distinct zones of the bilayered constructs, and the intermediate regions showed pre-hypertrophic chondrocyte gene expression, especially on the BdTCP constructs. Immunofluorescence analysis supported these observations. This study showed that the proposed bilayered scaffolds allowed a specific stimulation of the chondrogenic and osteogenic cells in the co-culture system together with the formation of an osteochondral-like tissue interface. Hence, the structural adaptability, suitable mechanical properties, and biological performance of the hierarchical scaffolds make these constructs a desired strategy for OC defect regeneration.